Margaret Cavendish : essential writings - Cunning, David (Oxford new histories of philosophy., 2019)
Margaret Cavendish, a 17th-century philosopher, scientist, poet, playwright, and novelist, went to battle with the great thinkers of her time, and in many cases arguably got the better of them, but she did not have the platform that she would have had in the 21st century. She took a creative and systematic stand on the major questions of philosophy of mind, epistemology, metaphysics, and political philosophy. This volume of Cavendish's writings provides a cross-section of her interconnected writings, views, and arguments.